Students’ Preferences towards Techniques Used by Lecturer in Teaching Pronunciation - Ariyanti Ariyanti; Umar Fauzan (CAKRAWALA LINGUISTA, 2018)
This study is aimed to explore techniques used by the lecturer in teaching pronunciation to EFL university students. In addition, the students’ preferences towards the techniques used by the lecturer are also pointed out by the use of direct observation to the classroom and semi-structured interview to the students. As a result, Oral Drill and Modeling appear to be the most techniques used by the lecturer and get the students’ preference in 20%. Meanwhile, the use of Real Object only appears once along the researchers’ observation which also takes 20% of the students’ preference. The last result which is obtained by the researchers is that the use of games attracts the students’ attention with 40% of preference. Interestingly, the students promote positive attitudes when the lecturer is applying the games to have them practice their pronunciation. They feel enjoyable and can acquire the pronunciation subject easier. Those findings imply that an evaluative assessment is needed in order to gain better quality of the students’ English pronunciation and reflect what technique seems to give more significant effect to the students’ production in pronunciation.